Anti-collapsin response mediator protein 5 encephalitis masquerading as a low-grade brain tumour. Issue 5 (31st May 2016) - Cope, Thomas E; Breen, David P; Chawda, Sanjiv; Cifelli, Alberto
Abstract : A 71-year-old woman presented acutely with seizures; her MRI suggested a low-grade glioma of the right temporal lobe. Over the preceding 18 months, she had developed progressive limb chorea and orofacial dyskinesia. Examination showed a predominantly amnestic cognitive profile. Initial investigations were normal, but later she was found to have antibodies to collapsin response mediator protein 5 (also called CV2). Her symptoms and neuroimaging abnormalities gradually improved without treatment. Four months later, surveillance imaging with 18 F-fluorodeoxyglucose-positron-emission tomography revealed a lesion confirmed by biopsy as a TX, N2, M0 small-cell lung cancer. This case is unusual for the strikingly unilateral neuroimaging abnormalities, which led to an initial misdiagnosis, and the spontaneous symptomatic improvement without treatment. In retrospect, the co-occurrence of paraneoplastic chorea, limbic encephalitis and neuropathy in the presence of an occult lung tumour make this almost a 'full house' of symptoms associated with antibodies to collapsin response mediator protein 5. It underlines the importance in clinical reasoning of avoiding the cognitive errors of premature closure and anchoring.